Confined crystallization and melting behaviors of poly(ethylene glycol) end‐functionalized by hydrogen bonding groups: Effect of contents for functional units. Issue 5 (8th October 2020) - Li, Xiang; Dong, Xiaolei; Zhou, Jiale; Bao, Jianna; Chen, Shichang; Lu, Wangyang; Zhang, Xianming; Chen, Wenxing
Abstract: The end group modification of hydrogen bonding units has a significant effect on physical properties of covalent linked polymers. In this study, telechelic poly(ethylene glycol)s (PEG) with various molecular weights were functionalized by thymine (Thy), which was able to form self‐complementary double hydrogen bonding. The physical properties of Thy‐functionalized PEGs, including viscosity in solution or melt state, crystallization behavior, crystalline structure as well as lamellar structure were systemically investigated by comparison with hydroxyl‐terminated PEGs. Crystallinity and melting temperature of linked PEG chains were decreased by the presence of Thy groups and the depression effects were strengthened by increase of Thy content. Crystallization rate and temperatures at which crystallization occurred were more complicated. Lower crystallization rate was obtained for Thy‐functionalized PEGs with highest Thy content, a signature for confined crystallization by covalent links to Thy groups. However, in the case of moderate Thy content, the trend of crystallization rate was shifted to lower temperature regions, where the maximum and minimum of crystallization rates were comparable with free polymer chains. For Thy‐functionalized PEGs with low Thy content, crystallization rates were similar with that of non‐functionalized PEGs. The differences in supercoolings might give explanation on differences in crystallization behaviors among three conditions. Abstract : For Thy‐functionalized poly(ethylene glycol) (PEG), the effect of Thy on the crystallization rate of PEG relied significantly on Thy content. The mobility constraints and the alteration of T m were the key factors behind the decreased crystallization rates and the shift of crystallization temperature region to lower temperature.